The Influence of Workforce Diversity on Employees’ Performance in Co-Operative Organizations of Kanchanpur - Saud, Dhan Bahadur (The Management Review, 2025)
Workforce diversity in cooperative organizations is a concept that has gained increasing significance in recent years. Cooperative organizations are typically structured around the principles of equality, democracy and solidarity and many of them have a long history of promoting diversity and inclusively within their membership and workforce. The background of workforce diversity in cooperative organizations can be traced back to the core values and principles that underpin the cooperative movement. The primary goal is to look into the relationship between workforce diversity and employee performance in the Kanchanpur district's cooperative organizations. The research design used in the study was descriptive. Using cluster and purposeful selection methods, 400 workers from various cooperative groups were chosen to participate in the survey. Data was collected using physical questionnaires and a structured questionnaire. To examine the impact of workforce diversity on employees' performance, regression analysis has been conducted. The findings showed that employees' performance is positively impacted by diversity in terms of gender, race, and job experience. Employee performance is also negatively impacted by physical disabilities. This study demonstrates how employee performance in Kanchanpur district cooperative organizations is impacted by workforce diversity. These findings can also be utilized to develop plans to enhance the way that current cooperative organizations implement staff diversity. This study looked at several facets of diversity and their connections to performance. For example, while physical problems have a detrimental effect on employees' performance, ethnicity, education, and job experience have a beneficial effect. Only the Kanchanpur cooperative in Nepal has taken this study into consideration; however, additional research can be conducted in other industries, such as manufacturing, hotels, hospitality, and other governmental and nongovernmental organizations.